The road to grace : the third journal of the walk series - Evans, Richard Paul. (New York : Simon & Schuster, 2012)
Now nearly halfway through his trek, Alan Christoffersen walks from South Dakota to Memphis, Tennessee. He covers more than 800 miles on foot, but it's the people he meets along the way who give the journey its true meaning.
Keywords: Executives -- Fiction; Life change events -- Fiction; Walking -- United States -- Fiction; Loss (Psychology) -- Fiction; Diaries -- Fiction